A Substage Increase in The AJCC Classification System Improves Prognostic Prediction in Stage III Gastric Cancer With Insufficient Lymph Nodes Removed - Zhao, Ri-Sheng; Liu, Yi-Nan; Dai, Wei-Gang; Chen, Si-Le; Ye, Jin-Ning; Zhai, Er-Tao; Cai, Shi-Rong; Chen, Jian-Hui (Frontiers in Oncology, 2021)
Background: The impact of lymph nodes (LNs) removed on the survivals of patients with stage III gastric cancer, especially on that of those who undergo the adjuvant chemotherapy as a compensation for a possibly insufficient lymphadenectomy, is still unclear. Methods: Consecutive patients (n=488) with stage III gastric cancer under R0 curative resection followed by adjuvant chemotherapy were analyzed. The overall survival (OS) was compared between patients with insufficient LNs removed (ILNr, <16 LNs) and sufficient LNs removed (SLNr, ≥16 LNs). Performance of the prediction systems was evaluated using the Likelihood ratio χ2 test, Akaike information criterion (AIC), Harrell’s concordance index (C-index), and area under the receiver operating characteristic curves (AUC). Results: The OS of patients were significantly longer in those with SLNr relative to those with ILNr (for stage IIIA, 68.2 vs. 43.2 months, P = 0.042; for stage IIIB, 43.7 vs. 24.9 months, P < 0.001; for stage IIIC, 23.9 vs. 8.3 months, P < 0.001; and for total stage III, 37.7 vs. 21.7 months, P < 0.001). However, the OS were similar between stage IIIA patients with ILNr and stage IIIB patients with SLNr (P = 0.928), between IIIB patients with ILNr and IIIC patients with SLNr (P = 0.962), and IIIC patients with ILNr and stage IV (P = 0.668), respectively. A substage increase in the AJCC classification system, from IIIA to IIIB, from IIIB to IIIC, and from IIIC to IV in patients with ILNr, enhanced the accuracy of prognostic prediction in patients with stage III gastric cancer compared to the current TNM system (Likelihood ratio χ2, 188.6 vs. 184.8; AIC, 4336.4 vs. 4340.6; C-index, 0.695 vs. 0.679, P = 0.002). The ROC curves revealed that the performance of prognostic prediction was better in the new prediction system (AUC=0.699) compared with the current TNM system (AUC=0.676) Conclusions: ILNr (LNs <16) impairs the long-term outcomes of stage III gastric cancer underwent adjuvant chemotherapy. The status of LNs removal adds values to the current TNM system in prognostic prediction of stage III gastric cancer.